O ensino de leitura em língua inglesa e a Teoria Dialógica do Discurso: um olhar sobre o cronotopo em livros didáticos da escola pública - Araújo, Alisson Gomes de (2023)
For Bakhtin (2018), any incursion into the field of meanings only takes place through chronotopes. When we consider the text, according to the assumptions of the Dialogical Discourse Theory, as a concrete utterance, we corroborate the Bakhtinian view that it is the place in which the subject and language, located in time and space, present themselves in its entirety. The utterance, as Brait (2010) recalls, is addressed to someone, it has an author and a recipient. In this scope, it is worth highlighting that the chronotope constitutes one of the key concepts in Bakhtin and the Circle’s thought and that it is currently an indispensable condition for a dialogical discourse analysis. In English language classes, especially in the work of teaching reading, the text demands from teachers, students and even textbooks, a movement towards conducting reading beyond the palpable instances, of what is visible in the utterance. According to Costa-Hübes (2017), we can consider that the utterance is established in a chronotope, an instance that provides it with the materiality of reality located in time and space. The central objective of this research is to analyze English language textbooks, especially the reading sections, from the perspective of the theoretical framework of the Dialogical Discourse Theory – DDT and the concepts that integrate Bakhtinian architecture. Taking as a basis the concept of chronotope, the prescriptions present in official documents (BNCC and DCRC) and the corpus composed of texts and reading activities present in English language books indicated by PNLD 2021, we can verify how the texts and activities present in the reading section develop from the chronotope, whether through linguistic-discursive elements, cultural aspects and the presence or absence of instructions that reveal to the teacher and the learning subject clues for the construction of meanings and the importance of understanding of spatio-temporal categories. The corpus for the analyzes was composed of three series of books from different publishers, which provided us with a more comprehensive view of the selected sample. The research also required the creation of a state of the art regarding the concept of chronotope, other key concepts for the studies of Bakhtin and the Circle, in addition to the development of an overview of the relevance of textbooks for the context of public schools and for teaching reading. The importance of bringing studies about the chronotope closer to the practice of teaching reading through textbooks was demonstrated, in addition to the relevance of the teacher's action in filling possible gaps in the analyzed materials. Keywords: dialogism; chronotope; textbook; English language; teaching reading.